Numerical Analysis of the Shear Behavior of Shallow-Wide Concrete Beams via the Concrete Damage Plasticity Model - Dejene, Hewan; Bogale, Muluken; Rynkovskaya, Marina (Civil Engineering Journal, 2025)
Shallow reinforced concrete beams are broadly used in buildings for their aesthetic and economic benefits, but their shear performance remains insufficiently known, especially considering the impact of stirrups. While experimental investigations provide a good understanding, they are expensive and provide limited insight, creating a gap in the understanding of the complex shear behavior of shallow RC beams. This study bridges this limitation by conducting finite element analysis and calibrating the critical concrete damage plasticity parameters such as the dilation angle, Kc values, eccentricity, damage parameters, and loading time. Additionally, the numerical model validated the experimental results by accounting for the effects of the stirrup spacing, width, and longitudinal-to-stirrup ratio to achieve the ultimate load and corresponding deflection differences within 1.69% and 10.7%, respectively. The findings revealed that increasing the stirrup spacing enhanced ductility without increasing strength, whereas increasing the beam width and longitudinal-to-stirrup ratio increased strength and ductility. Finally, a comparison with design codes and machine learning revealed greater accuracy of FEA prediction, presenting new insight into upgrading the design code for shallow RC beams. Doi: 10.28991/CEJ-2025-011-02-022 Full Text: PDF